1999
DOI: 10.1016/s0002-9440(10)65210-8
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Gene Network Connected to Interferon-γ in Liver Regeneration from Oval Cells

Abstract: Suppression subtractive hybridization was used to clone genes associated with proliferation of oval cells in rat liver regenerating after a 70% partial hepatectomy combined with the feeding of 2-acetylaminofluorene. A subset of the identified genes comprised interferon-gamma receptor alpha subunit (IFN-gammaRalpha), gp91phox, interleukin-1beta (IL-1beta), lymphocyte function-associated molecule-1alpha (LFA-1), eukaryotic initiation factor-2-associated 67-kd protein (eIF-2-associated 67-kd protein), and alpha-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
43
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 34 publications
11
43
1
Order By: Relevance
“…It is also possible that these cytokines are involved in paracrine signaling of oval cells, because we demonstrate that all three transcripts are abundant in purified oval cells, and it has been shown by Bisgaard et al 15 that IFN␥ receptor subunits are expressed by oval cell ductular structures after their induction by 2-acetylaminofluorene coupled with PHx.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…It is also possible that these cytokines are involved in paracrine signaling of oval cells, because we demonstrate that all three transcripts are abundant in purified oval cells, and it has been shown by Bisgaard et al 15 that IFN␥ receptor subunits are expressed by oval cell ductular structures after their induction by 2-acetylaminofluorene coupled with PHx.…”
Section: Discussionsupporting
confidence: 68%
“…Subtractive hybridization comparing transcripts from nonparenchymal cells after 2-acetylaminofluorene coupled with PHx and PHx-identified genes induce IFN␥, IFN␥ receptor subunits 1 and 2, primary and secondary response genes, and IFN␥-induced cell adhesion molecules. 15 Using a liver progenitor cell line, PIL-2, 28 we showed IFN␥ rapidly induces STAT-3 phosphorylation when it is added to cultures. This result suggests a direct effect of IFN␥ in activating this signaling pathway that, in several in vitro studies, is shown to link cytokine signaling with cell proliferation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…14 The cDNA for rat Thy-1 encompassed nucleotides 46 to 531 (GenBank accession no. NM_012673), and for ␣-fetoprotein (AFP), nucleotides 101 to 329 (GenBank accession no.…”
Section: Northern Blot Analysismentioning
confidence: 99%
“…48 Suppression subtractive hybridization following 2-AAF/PH identified genes associated with the proliferation of oval cells including IFN-g, IFN-g receptor a subunit (IFN-gRa), IFN-gRb primary response genes (gp91phox), IFN-gRb secondary response genes such as ICE, CD54/ICAM-1 and uPAR, cytokines that induce expression of IFN-g, which include IL1-b and IL-18, and cell adhesion molecules that regulate the interactions between lymphocytes and epithelial cells; lymphocyte functionassociated molecule 1-a (LFA-1a/CD11 and CD54/ ICAM-1). These proteins are all part of the complex cellular response associated with the IFN-g signaling cascade.…”
Section: Role Of Inflammatory Cytokinesmentioning
confidence: 99%